CODE-CROSSING: HIERARCHICAL POLITENESS IN JAVANESE - Wajdi, Majid; Darma Laksana, I Ketut; Suastra, I Made; Budiarsa, I Made (e-Journal of Linguistics; Vol.7. Januari 2013 No. 1)
Javanese is a well known for its speech levels called ngoko ‘low’ and krama ‘high’ which enable its speakers to show intimacy, deference, and hierarchy among the society members. This research applied critically Brown and Gilman (1960)’s theory of terms of address to analyze the asymmetrical, factors which influence, and politeness of the use of speech levels in Javanese.                                                                                                   Method of observation, in depth interview, and document study were applied to collect the data. Recorded conversation was then transcribed into written form, classified and codified according to the speech levels, and analyzed using politeness system (Scollon and Scollon, 2001) and status scale (Homes, 2001).                                                                       The use of speech levels shows asymmetric communication: two speakers use two different codes, i.e. ngoko and krama because of power (+P) and with/without distance (+/-D), and it is the reflection of hierarchical politeness. The asymmetrical use of ngoko and krama by God and His Angel, God and human beings strongly explicated the asymmetrical communication between superiors and inferiors. The finding of the research shows that the use of ngoko and krama could present the phenomena of code-switching, code-mixing, and the fundamental phenomenon is ‘code-crossing’. It is concluded that hierarchical politeness in Javanese is ‘social contract’ i.e. the acknowledgment of the existence of high class (superior) and low class (inferior)  implemented in ‘communications contract’  using speech levels of the Javanese language  in line with status scale. Asymmetrical use of ngoko and krama indexed inequality, hierarchy, and harmony
Keywords: asymmetric, code-crossing, hierarchy, Javanese, speech levels